B) 90 − (8a + 9) = (11 + 2a)
C) (11 + 2a) − 90 = (8a + 9)
D) (8a + 9) − (11 + 2a) = 90
Answer:
B
Step-by-step explanation:
Seeing the above angles we conclude that
(11+2a)+(8a+9)=90 (since they are complementary angles)
So
Subtracting (8a+9) to both sides we get
90-(8a+9)=11+2a
Answer:
The answer is B.) 90 - (8a + 9) = (11 + 2a)
Step-by-step explanation:
90 − (8a + 9) = (11 + 2a)
Complementary angles add to 90°
I will Give BRAINLIEST
Answer:
e) 1
f) -207
g) -10
h) 29/40
Step-by-step explanation:
e) 10-3×3
f) -27×(11/3+4)
g) -(10)
h) -7/5+11/4-5/8
answer: e) 1
f) -207
g) -10
h) 29/40
Step-by-step explanation:
e) 10-3×3
f) -27×(11/3+4)
g) -(10)
h) -7/5+11/4-5/8